Book Review ~ The Strategic Use of Learning Technologies. Editor: Elizabeth J. Burge - Reviewed by Wim Van Petegem (International Review of Research in Open and Distributed Learning, 2003)
The editor defines the term learning technology as “any tool that requires informed design and appropriate use in order to enhance an adult’s ability to learn – i.e., to enhance the use of various information processing strategies and learning activities alone, with peers, and with appropriate advisers and educators.” With this definition in mind, all authors focus their contribution on learners and learning services or activities as key issues – not technology as such, but the use of technology for learning purposes. So far, the title covers the contents of the book. Unfortunately, from my perspective, the book falls short of explaining or offering more insight in the strategic aspects.